Determinan Permintaan Jasa Transportasi Penyeberangan Antar Pulau Di Pelabuhan Marampa Kabupaten Manokwari - Marcus R. Maspaitella; Ketysia Imelda Tewernussa; Rizza Siwalette (JFRES Journal of Fiscal and Regional Economy Studies, 2019)
This study aims to determine the effect of ticket prices, income levels and service quality on demand for interisland crossing transportation services in Marampa Port, Manokwari Regency. The sample of this study was 75 passenger respondents. Data analysis in this study uses multiple linear regression analysis. The results showed that the level of income had a significant effect on demand for inter-island crossing transportation services at Marampa Port in Manokwari, while ticket prices and service quality did not have a significant effect. The implication of this research is that the substitution of other modes of transportation can occur if there is an increase in the level of passenger income. In addition, improving the quality of services needs to be continued both by the local government and the port administrator.